Fake news in healthcare: A study on the spread of false information on social media and the need for adjustments in Brazilian legislation (Research, Society and Development, 2025)
The aim of this study is to identify characteristics and develop models that help understand how fake news spreads on social media, highlighting mechanisms to improve legislation aimed at combating its dissemination in defense of public health. The research method was divided into three stages: (1) review of current legislation addressing the dissemination of fake news; (2) application and evaluation of responses to a sociocultural questionnaire using multivariate factor analyses and machine learning to identify possible relationships between the behavior of spreading false information and sociocultural characteristics; and (3) identification of parameters associated with the spread of fake news using a complex networks approach. The results show that Brazilian legislation still lacks mechanisms to characterize intent (dolo) in the context of fake news dissemination on social networks. The questionnaire responses indicate that the spread of fake news is not primarily due to a lack of knowledge. The analysis of fake news propagation on social networks revealed that its dissemination does not follow the typical pattern of scale-free networks, suggesting artificial boosting of content. Additionally, the use of complex network theory to analyze propagation parameters can objectively identify whether dissemination occurs naturally or artificially. Holding individuals legally accountable for the intentional spread of fake news on social media requires adjustments to current legislation.